Evaluation Of Mrna Vaccines Against Viral Infections: Efficacy, Limitations, And Future Prospects (The Review of Diabetic Studies, 2024)
Messenger RNA (mRNA) vaccines have emerged as a transformative platform in the prevention and control of viral infections, demonstrating remarkable efficacy during the COVID-19 pandemic. Unlike traditional vaccines, mRNA vaccines utilize synthetic messenger RNA to encode viral antigens, enabling rapid development, scalable manufacturing, and strong immunogenicity. This review evaluates the efficacy of mRNA vaccines against viral infections, highlights their immunological advantages, and examines key limitations associated with their widespread use. Clinical and real-world data indicate that mRNA vaccines induce robust humoral and cellular immune responses, providing high levels of protection against severe disease and mortality. However, challenges such as cold-chain requirements, reactogenicity, durability of immune protection, viral variants, and global accessibility remain significant barriers. Additionally, concerns related to long-term safety, vaccine hesitancy, and manufacturing costs warrant further investigation. Despite these limitations, ongoing advancements in mRNA design, delivery systems, and thermostable formulations are expanding the potential of this platform beyond COVID-19 to include influenza, HIV, Zika, and other emerging viral threats. Overall, mRNA vaccine technology represents a major milestone in vaccinology, offering a flexible and powerful approach for rapid response to current and future pandemics. Continued research and innovation are essential to overcome existing challenges and fully realize the global public health potential of mRNA vaccines.